Design and develop home security system - Lim Siew Chiat (School of Electrical System Engineering, University Malaysia Perlis, 2011)
Nowadays, the burglary crime is increasing every year. Security system is very important to be installed. However, many families cannot afford to do so. Therefore, this Final Year Project is to design and develop a low-cost home security system using microcontroller. This home security system is provided with keypad to prevent intruder from entering the home, a keypad is installed at the side of the front door. Password is needed to be key in to open the door. Besides that, micro switches are equipped on all windows. This is a closed-loop system which the alarm will be triggered if the window has been opened. In addition, PIR sensor is also developed to detect whether there is any intruder already inside the house. Besides protecting the home owners from intruder, temperature sensor will be installed in kitchen to give alert to the home owners so that fire can be prevented. In this project, C language will be used in all the programming to control the whole system. Any of the sensors above can give input to the system to sound the alarms. The home owners can enable and disable the system manually. This project is a low-cost home security system which is affordable by most home owners and the system is user-friendly.